Artificial Intelligence Logic and Applications The 3rd International Conference, AILA 2023, Changchun, China, August 5-6, 2023, Proceedings - Zhang, Songmao; Zhang, Yonggang (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book constitutes the proceedings of the Third International Conference, AILA 2023, held in Changchun, China, during August 5-6, 2023. The 26 full papers and the 10 short papers included in this volume were carefully reviewed and selected from 56 submissions. This volume aims to provide novel ideas, original research achievements, and practical experiences in a broad range of artificial intelligence logic and applications.
AI Logic Foundation -- AI Logic Reasoning -- AI Logic Applications.
Keywords: Machine theory; Computer science; Artificial intelligence; Computer science -- Mathematics; Software engineering; Formal Languages and Automata Theory; Theory of Computation; Artificial Intelligence; Mathematics of Computing; Software Engineering